THE IMPACT OF ONLINE-BASED LOANS ON COMMUNITY WELFARE IN BOGOR DISTRICT (Study on The Community of Gobang Village, Bogor District) - Aziz Annoval; Dina Hendiyani (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
The aim of this research is to determine the impact of online-based loans on the community in Gobang Village, Bogor Regency and to determine the factors that cause people in Gobang Village, Bogor Regency to take online-based loans in terms of Islamic economics. This type of research is field research (direct research in the field) with a qualitative approach. The data sources used are primary data and secondary data, with data collection techniques through observation, interviews and documentation. The data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of this research are: 1) The impact of online-based loans for the community in Gobang Village, Bogor Regency, namely that the positive impact is that the procedure for borrowing money in online-based applications is an easier process and the money is disbursed quickly, and their emergency funding needs or requirements can be met quickly . Meanwhile, the negative impacts are administrative deductions that reach 30% of the principal amount of the loan, the large amount of interest charged to consumers, plus large daily fines if consumers are late in paying, misuse of personal data and personal information of online loan application service users (consumers), and inhumane debt collection methods for consumers who are late in paying loan installments, such as threatening/intimidating or verbally abusing them, distributing consumers' personal data on social media to be publicly humiliated; 2) Factors that cause people in Gobang Village, Bogor Regency to make online-based loans in Islamic economics, namely the procedure for borrowing money in online-based applications is an easier process and the money is disbursed quickly, loans are made due to pressing needs or the need for emergency funds. However, in practice, online-based loans have a huge negative impact on consumers, so that the practice of using online loan applications is contrary to the aim of Islamic economics, namely mashlalah (benefit) for mankind, and also contrary to one of the principles of Islamic business ethics which is is part of Islamic economics, namely equilibrium.